Motherhood Delay and the Human Capital of the Next Generation - Miller, Amalia R (American Economic Review, 2009)
This paper exploits biological fertility shocks as instrumental variables to estimate the effect of motherhood delay on the cognitive ability of the next generation. Using detailed panel data on women in the NLSY79 and their first-born children aged 5 to 14, we find a year of delay leads to significant increases in math and reading scores: a 7 year delay produces gains on par with the black-white score difference. These results reveal a potential weakness of pro-natalist policies promoting early motherhood. While such policies may increase total period fertility rates, they will be less effective at increasing total human capital.